(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article delves into the intricate interconnection among lexical, textual, and logical significances within the realm of artistic discourse. Through a thorough investigation, the study endeavors to clarify the manner in which lexical selections, textual configurations, and logical deductions collectively influence the overarching process of signification in artistic endeavors. By scrutinizing diverse instances spanning various artistic mediums, the research endeavors to illuminate the intricate correlation between linguistic expression, textual composition, and conceptual cohesion in the domain of art.